Novel NUDT2 variant causes intellectual disability and polyneuropathy. Issue 11 (15th October 2020) - Diaz, Frank; Khosa, Shaweta; Niyazov, Dmitriy; Lee, Hane; Person, Richard; Morrow, Michelle M.; Signer, Rebecca; Dorrani, Naghmeh; Zheng, Allison; Herzog, Matthew; Freundlich, Robert; ,; et al.
Abstract: Exome or genome sequencing was performed to identify the genetic etiology for the clinical presentation of global developmental delay, intellectual disability, and sensorimotor neuropathy with associated distal weakness in two unrelated families. A homozygous frameshift variant c.186delA (p.A63Qfs*3) in the NUDT2 gene was identified in cases 1 and 2 from one family and a third case from another family. Variants in NUDT2 were previously shown to cause intellectual disability, but here we expand the phenotype by demonstrating its association with distal upper and lower extremity weakness due to a sensorimotor polyneuropathy with demyelinating and/or axonal features.